DRB1*03:01 Haplotypes: Differential Contribution to Multiple Sclerosis Risk and Specific Association with the Presence of Intrathecal IgM Bands - de la Concha, Emilio G.; Cavanillas, María L.; Cénit, M. Carmen; Urcelay, Elena; Arroyo, Rafael; Fernández, Óscar; Álvarez-Cermeño, José C.; Leyva, Laura; Villar, Luisa M.; Núñez, Concepción (PLOS ONE, 2012)
Background Multiple sclerosis (MS) is a multifactorial disease with a genetic basis. The strongest associations with the disease lie in the Human Leukocyte Antigen (HLA) region. However, except for the DRB1*15:01 allele, the main risk factor associated to MS so far, no consistent effect has been described for any other variant. One example is HLA-DRB1*03:01, with a heterogeneous effect across populations and studies. We postulate that those discrepancies could be due to differences in the diverse haplotypes bearing that allele. Thus, we aimed at studying the association of DRB1*03:01 with MS susceptibility considering this allele globally and stratified by haplotypes. We also evaluated the association with the presence of oligoclonal IgM bands against myelin lipids (OCMB) in cerebrospinal fluid. Methods Genotyping of HLA-B, -DRB1 and -DQA1 was performed in 1068 MS patients and 624 ethnically matched healthy controls. One hundred and thirty-nine MS patients were classified according to the presence (M+, 58 patients)/absence (M−, 81 patients) of OCMB. Comparisons between groups (MS patients vs. controls and M+ vs. M−) were performed with the chi-square test or the Fisher exact test. Results Association of DRB1*03:01 with MS susceptibility was observed but with different haplotypic contribution, being the ancestral haplotype (AH) 18.2 the one causing the highest risk. Comparisons between M+, M− and controls showed that the AH 18.2 was affecting only M+ individuals, conferring a risk similar to that caused by DRB1*15:01. Conclusions The diverse DRB1*03:01-containing haplotypes contribute with different risk to MS susceptibility. The AH 18.2 causes the highest risk and affects only to individuals showing OCMB.